A escolinha de arte de Cachoeiro de Itapemirim : resgate de uma história - Oliveira, Myriam Fernandes Pestana (2013)
This research proposes to answer the following question: How did the Art School of Cachoeiro de Itapemirim – EACI join the Art School movement in Brazil-EAB, and what was the role of Professor Isabel Braga in the dissemination and implementation of this school? The goal is to know, in order to understand the role played by the educator Isabel Braga on the EACI and which art education proposal was offered in the EACI. To answer this question a history rescue of the creation and the operation of this School was made, as well as the influence and cooperation of Professor Augusto Rodrigues, creator of EAB. Therefore, for the development of this research, which is qualitative in nature, it was necessary to have bibliographic survey about Brazil’s Art School from materials published in books, scientific articles, and journals. Due to the lack of studies on the EACI, other technical procedure used, was the documentary research. The investigations started from material found in particular collection and reports of people involved in the issue. So, this history is told from documentary and verbal information, and became possible by the methodology of the “Annales School”, the New History of Bloch and Febvre (2001). As theoretical framework, the English philosopher Herbert Read (1981,1986, 2001) responsible for the movement Educations through Art(1943).Since it is an exploratory and bibliographical research, the documents used as support, are analyzed from the greimasiana, semiotics (Landowski, 1992). To rescue the EAB educational movement, a tour of the art teaching and learning was made and also analysis of different texts (documents, pamphlets, testimonials) of the EACI. Through this textual dialogic interweaving, a historical rescue occurred what made the history of the Art School of Cachoeiro de Itapemirim able to be retold and moreover, assured to be part of a movement that was a landmark in the art teaching of Brazil. We can say that the EACI, even with the short time it lasted, led their students, children, adolescents and adults to experience the freedom of expression and aesthetic education guided in education of the senses, as well as to highlight the pioneering, in the teaching learning of the art in Espírito Santo.